A Challenges–Adaptive Mechanisms–Results (CARE) Model for Indonesian Entrepreneurs with Disabilities - Maris, Anis Wahyu Intan; Rahmi, Iftita (Jurnal Manajemen Teknologi, 2022)
Abstract. This article explores challenges that motivate persons with disabilities to engage in entrepreneurship and adaptive mechanisms to overcome their challenges. The study expands the understanding of the initial challenges-adaptive mechanisms-results (CARE) model by including entrepreneurs with different disabilities who deal with various challenges and adaptive mechanisms to attain social, personal, and business-related goals. We conducted semi-structured interviews to explore the lived experiences of nine entrepreneurs with physical, sensory, or mental disabilities. Our empirical findings indicate that difficulties at the personal level decreased all respondents' job opportunities, which encouraged them to become entrepreneurs in striving for independent living. We find support from their circle, education, and technological advancements to have been the most effective adaptive mechanism strategies leading their entrepreneurial activities to success. The expanded CARE model contributes to the literature on entrepreneurship for persons with disabilities and provides insights potentially for all stakeholders supporting the entrepreneurial ecosystem for persons with disabilities.Keywords: Challenges, adaptive mechanism, disability, disabled entrepreneurs, entrepreneurshipAbstrak. Artikel ini mengeksplorasi tantangan yang memotivasi penyandang disabilitas untuk terlibat dalam kewirausahaan dan mekanisme adaptif untuk mengatasi tantangan mereka. Studi ini memperluas pemahaman tentang model tantangan - mekanisme adaptif - hasil (CARE) dengan melibatkan pengusaha dengan ragam disabilitas berbeda yang menghadapi berbagai tantangan dan mekanisme adaptif untuk mencapai prestasi sosial, bisnis, dan pribadi. Penelitian ini melakukan wawancara semi terstruktur untuk menggali pengalaman hidup sembilan pengusaha penyandang disabilitas fisik, sensorik, dan mental. Berdasarkan temuan empiris kami, kesulitan di tingkat pribadi menurunkan semua peluang responden untuk mendapatkan pekerjaan di tempat kerja. Fakta ini mendorong mereka untuk menjadi wirausahawan untuk berjuang hidup mandiri. Dukungan dari kalangan mereka, pendidikan, dan kemajuan teknologi merupakan strategi mekanisme adaptif yang paling efektif yang mengantarkan kegiatan wirausaha mereka menuju kesuksesan. Model CARE yang diperluas berkontribusi pada literatur tentang kewirausahaan bagi penyandang disabilitas dan memberikan wawasan kepada semua aktor penting dalam mendukung ekosistem kewirausahaan bagi penyandang disabilitas.Kata kunci: Tantangan, mekanisme adaptasi, disabilitas, wirausahawan difabel, kewirausahaan.